2018
DOI: 10.1002/joc.5419
|View full text |Cite
|
Sign up to set email alerts
|

Activity of the Southern Annular Mode during 2015–2016 El Niño event and its impact on Southern Hemisphere climate anomalies

Abstract: Previous studies documented that El Niño (EN) events are in general associated with negative phases of the Southern Annular Mode (SAM). EN 2015–2016 (EN15–16) was one of the three strongest events ever recorded. However, it was associated with a SAM positive phase of extreme intensity. Furthermore, while the negative linear relationship between ENSO and SAM during the most recent period (1986–2014) was significant and associated with a narrow uncertainty band, the combined condition of both climate patterns in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 16 publications
1
20
1
1
Order By: Relevance
“…The similar classification accuracies found in 2013 and 2016 provide the first evidence that otolith morphological differences among zones were not sensitive to the El Niño event, which dominated the oceanographic conditions during 2014-16 in the Southern Hemisphere (Vera and Osman 2018). This finding suggests the absence of a generalised movement and mixing of schools in a southward direction, which could be expected as a result of movement of warm water masses from north to south.…”
Section: Population Structure and Spatial Segregation Of Anchovetasupporting
confidence: 61%
“…The similar classification accuracies found in 2013 and 2016 provide the first evidence that otolith morphological differences among zones were not sensitive to the El Niño event, which dominated the oceanographic conditions during 2014-16 in the Southern Hemisphere (Vera and Osman 2018). This finding suggests the absence of a generalised movement and mixing of schools in a southward direction, which could be expected as a result of movement of warm water masses from north to south.…”
Section: Population Structure and Spatial Segregation Of Anchovetasupporting
confidence: 61%
“…Byrne et al (2017) attempted this separation in observations via a regression-based approach and concluded that the stratospheric pathway was dominant. More recent work by Vera and Osman (2018), who showed that the "failed" zonally symmetric response to the large El Niño of 2015/2016 was consistent with an exceptionally strong SPV, also supports this conclusion.…”
Section: 1029/2018jd030173mentioning
confidence: 65%
“…Results here show a strong SAM influence together with an expansion of the semi-permanent subtropical anticyclones in the South Atlantic and South Indian Oceans as key factors for a poleward deviation of moisture corridors, and consequently for the regional drying trend which culminated in the 'Day Zero' water crisis. In fact, Vera and Osman (2018) have shown a decoupling of a previously strong link between El Niño and the negative phase of SAM since 2015. Given that the subtropical anticyclones are expected to expand further poleward under climate change (despite disparate observational-based rates of expansion-e.g.…”
Section: Discussion and Summarymentioning
confidence: 99%